'Pathologising' grief: An exploration of public expectations and grieving norms - Penman, Emma; Breen, Lauren; Hewitt, Lauren; Prigerson, H. (Australian Centre for Grief and Bereavement, 2014)
The Diagnosis of Grief. Expressions of grief in Western society are shaped by shared expectations of what is considered appropriate in light of characteristics of the mourner, the deceased, and the circumstances of the death (Doka, 1989). These, in turn, influence the expectations that bereaved people have of themselves and thus their experience of grief (Breen and O'Connor, 2010). In determining if and when a grief reaction is 'normal' or 'pathological', definitions of mental disorder stipulate that symptoms must deviate from social norms (American Psychology Association [APA], 2013). There is, however, little understanding of the norms for 'normal' grief or attitudes towards grief as a proposed mental disorder in future editions of the Diagnostic and Statistical Manual of Mental Disorders (DSM) and International Classification of Diseases (ICD-10; Prigerson et al., 2009). It is reasonable to assume that discrepancies between public opinion and diagnostic criteria will influence the acceptance of this proposed disorder. The aim of this study was to examine the public norms and expectations of grief following bereavement and determine the factors that influence these norms.